2008
DOI: 10.1080/17453670710014815
|View full text |Cite
|
Sign up to set email alerts
|

Cement is recommended in intralesional surgery of giant cell tumors: A Scandinavian Sarcoma Group study of 294 patients followed for a median time of 5 years

Abstract: Background Giant cell tumors of bone rarely metastasize but often recur locally after surgery. There is limited knowledge about the risk of recurrence related to different types of treatment.Patients and methods We analyzed factors affecting the local recurrence rate in 294 patients with giant cell tumors of the extremities using prospectively collected material from 13 centers. The median follow-up time was 5 (0.2-18) years.Results A local recurrence was diagnosed in 57 of 294 patients (19%). The overall 5-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
205
7
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 207 publications
(241 citation statements)
references
References 33 publications
(49 reference statements)
15
205
7
11
Order By: Relevance
“…Some studies have reported a lower risk of local recurrence with the use of PMMA for curetted cavities [2,4,20,21]. However, we found that tumor recurrence for patients who received PMMA did not differ from patients who underwent a bone graft.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Some studies have reported a lower risk of local recurrence with the use of PMMA for curetted cavities [2,4,20,21]. However, we found that tumor recurrence for patients who received PMMA did not differ from patients who underwent a bone graft.…”
Section: Discussioncontrasting
confidence: 63%
“…In addition, delayed recurrence has been reported as much as 20 years after treatment [45]. However, 75% to 80% of patients have experienced recurrence of GCTs within 2 years [14,19,20,26,40]. Sixth, different adjuvants were used (eg, phenol, cryosurgery, high-speed burr) in the curettage group reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…Giant cell tumor is difficult to treat, but preservation of the joint through extensive curettage should be considered a priority [11]. This condition usually leaves a large cortical defect originating either by aggressive tumor growth or by the surgeon in an attempt to obtain adequate access to the tumor cavity while performing the curettage.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of giant cell tumors (GCTs) remains a difficult problem and surgical options are intralesional excision (curettage) or en bloc resection of the tumor [6,7,9,11,14,16,20,22]. Curettage is the most attractive method because it preserves autologous structures, bone architecture, and native joint cartilage; however, a higher rate of local tumor recurrence has been reported with this method [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation